Diazapentacenes from Quinacridones - Wiesner, Thomas; Ahrens, Lukas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
Bis(silylethynylated) 5,7- and 5,12-diazapentacenes were synthesized from cis- and trans-quinacridone using protection, alkynylation and deoxygenation. The solid-state packing of the targets is determined by choice and position of the silylethynyl substituents. The position of the substituents and nitrogen atoms influence the optical properties of the targets.